Gerontology Days 2024 International Scientific Conference. The Faculty of Health Sciences at the University of Debrecen Deartment of Gerontology and Dementia Studies, Faculty for Social Wellbeing at the University of Malta 11. October 2024. (online) - Bene, Ágnes (Magyar Gerontológia, 2024)
Conference Programme